Quantum Optimal Control Problems with a Sparsity Cost Functional. (2nd August 2016) - Ciaramella, Gabriele; Borzì, Alfio
ABSTRACT: In this article, the investigation of a class of quantum optimal control problems with L 1 sparsity cost functionals is presented. The focus is on quantum systems modeled by Schrödinger-type equations with a bilinear control structure as it appears in many applications in nuclear magnetic resonance spectroscopy, quantum imaging, quantum computing, and in chemical and photochemical processes. In these problems, the choice of L 1 control spaces promotes sparse optimal control functions that are conveniently produced by laboratory pulse shapers. The characterization of L 1 quantum optimal controls and an efficient numerical semi-smooth Newton solution procedure are discussed.